Restorative Justice as an Alternative to Criminal Punishment: Global Perspectives and Local Adaptations - Mulyadi, Tri; Santosa, Tomi Apra (Indonesian Research Journal on Education, 2025)
Restorative justice has developed into one of the alternative approaches in the modern criminal justice system that focuses on restoring social relationships rather than simply punishing criminals. This study aims to analyze the application of restorative justice as an alternative to criminal punishment by reviewing global perspectives and its adaptation in the local context. This study uses qualitative methods with a literature review approach and comparative analysis of various restorative justice practices in developed and developing countries. The results show that the global application of restorative justice emphasizes the principle of active participation between perpetrators, victims, and communities in the process of resolving legal conflicts, with the main objective of achieving a more humane, inclusive, and sustainable justice. At the local level, the adaptation of restorative justice requires attention to the prevailing social, cultural, and legal contexts. The integration of local values and cultural wisdom is an important factor in developing an effective conflict resolution model that is acceptable to the community. The application of mechanisms such as penal mediation, diversion, and peace forums has been proven to reduce the burden on the criminal justice system, accelerate the case resolution process, and reduce recidivism rates. This study also highlights the challenges in harmonizing the restorative justice approach with positive law, including regulatory aspects.